PEMAHAMAN BIDAN TENTANG PERATURAN MENTERI KESEHATAN REPUBLIK INDONESIA TENTANG IJIN DAN PENYELENGGARAAN PRAKTIK BIDAN - Hastuti, Puji; Yuliani, Diki Retno; ., Rusmini (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
The practice of midwifery services are health services that have a significant contribution in improving health, especially maternal and child health. For that a midwife should be able to maintain the quality and safety by providing services in accordance with the authority , based on the regulatory services practice clear. This study aims to describe the midwife understanding of the Regulation of the Minister of Health of the Republic of Indonesia Number 1464/MENKES/PER/X/2010 of Permit and Implementation Practice Midwife in Banyumas.This research is a descriptive cross- sectional design . The population in this research that the whole midwife working in the area of ​​Banyumas Health Office 728 samples of 88 people with a midwife . Sampling technique with accidental sampling. Results showed the most understanding about licensing midwives high enough minimum of 67% less by 5 % . Understanding of the implementation of good practices the highest and lowest 49 % less 3 % . Understanding midwife about recording and reporting the highest good and the lowest 94 % less than 6 % . An understanding of the guidance and supervision of midwives the most high enough 55 % and the lowest approximately 9 % . An understanding of the midwives Ministry of Health of the Republic of Indonesia 1464/menkes/per/x/2010 number of licenses and the implementation of midwifery practices in the highest category of Banyumas regency enough and the lowest 55 % less 3 %. Suggestions addressed to the midwife for more active in seeking information and for further research using better sampling techniques with other variables such as the implementation of Regulation of the Minister of Health of the Republic of Indonesia Number of licenses and implementation 1464/MENKES/PER/X/2010 midwife practice in Banyumas district . Keywords : Regulation of the Minister of Health of the Republic of Indonesia No. 1464/2010, Midwives